Appropriate Complementary Feeding Among Indonesian Children Aged 6-23 Months: A Descriptif Literature Review - Suyitno, Suyitno; Maretalinia, Maretalinia; Khan, Muhammad Uzair; supriatin, Supriatin (Ahmar Metastasis Health Journal, 2024)
The introduction of complementary foods (CF), which includes solid and semi-solid foods alongside breastfeeding, is crucial for ensuring adequate nutrition and supporting healthy growth and development in children aged 6-23 months. In Indonesia, a country with diverse cultures and socioeconomic conditions, family dynamics significantly influence practices and choices related to CF. These factors collectively shape the nutritional status and health outcomes of children during this critical developmental period. This descriptive literature review was conducted by searching electronic databases such as PubMed, Google Scholar, and local Indonesian academic repositories. Keywords used included "complementary feeding," "family dynamics," "child nutrition," and "Indonesia." The review focused on studies published in the last ten years to ensure relevance and timeliness. The results indicate that inappropriate CF practices, such as the early or late introduction of solid foods and a lack of food diversity, contribute to malnutrition. Nutritional status in this critical age group is heavily influenced by the type and timing of CF, with children receiving diverse and timely foods showing better growth outcomes. CF practices are also closely related to the incidence of diarrhea in infants. Factors such as the child's age, nutritional status, breastfeeding practices, and hygiene can affect the risk of diarrhea. Educational interventions and the provision of fortified foods can improve the growth and micronutrient status of children aged 6-23 months. Findings from various studies highlight the crucial role of appropriate CF practices in influencing the nutritional status, growth, and overall health of children aged 6-24 months. Comprehensive strategies that include education, fortification, and the promotion of local food cultures are essential for improving the nutritional outcomes and development of young children.